Lepidochitona Gray 1821 - Reyes-Gómez, Adriana; Vargas-Ponce, Ofelia; Galván-Villa, Cristian; Salgado-Barragán, José; Esqueda-González, Ma. Del Carmen; Ríos-Jara, Eduardo (Zenodo, 2023)
Lepidochitona Gray, 1821 Type material and locality. Chiton marginatus Pennant, 1777 = Chiton cinereus Linnaeus, 1767: 1–532, accepted as Lepidochitona cinerea (Linnaeus, 1767). Norwegian sea. Based on molecular studies, Eernisse (2007) reestablished the genus Cyanoplax and assigned the Lepidochitona species of the West Coast of the United States to a lineage independent from the Atlantic and Mediterranean species. Accordingly, Lepidochitona beanii (from the Gulf of California) and the Caribbean Lepidochitona species are retained as members of the genus Lepidochitona , and the genus Nutallina has been identified as the sister group to Cyanoplax. Published as part of Reyes-Gómez, Adriana, Vargas-Ponce, Ofelia, Galván-Villa, Cristian, Salgado-Barragán, José, Esqueda-González, Ma. Del Carmen & Ríos-Jara, Eduardo, 2023, Inventory of chiton species (Polyplacophora) from the rocky intertidal of the Northern Gulf of California, with an illustrated taxonomic key, pp. 147-178 in Zootaxa 5296 (2) on page 162, DOI:10.11646/zootaxa.5296.2.2, http://zenodo.org/record/7973065